NATIONAL-CULTURAL CHARACTERISTICS OF THE FEMALE IMAGE IN MARGARET DRABBLE’S FICTION - Axmedjanova Farida Djavairovna (International Journal of Literature and Language Studies, 2026)
This article presents a comparative analysis of the female concept in the works of O‘tkir Hoshimov and Margaret Drabble. The study examines the representation of women from cultural, social, and psychological perspectives, focusing on themes such as motherhood, female identity, moral values, and personal autonomy. Through the analysis of selected works, the research reveals that Hoshimov portrays women primarily as symbols of family, sacrifice, and spiritual resilience, whereas Drabble emphasizes women’s individuality, self-realization, and intellectual independence. Despite differences in cultural and ideological contexts, both writers depict women as complex and multidimensional figures whose experiences reflect broader social transformations and human values. The findings demonstrate that the female concept occupies a central position in the artistic worldviews of both authors and serves as an important means of expressing cultural identity and social change.